Enhancement in the magnetic and electrical conductivity properties of PVA- black tea composite films. (15th March 2019) - Mahender, C; Soam, Ankur; Ade, Ramesh; Vadla, Sambasiva; Nayak, S; Nanda, J; Sumangala, T P
Abstract: Cost-effective conducting polymer composite films were prepared from non-conducting polymer and black Tea. The films showed conducting and considerable magnetic properties. The measured coercive field, saturation magnetization and remnant magnetization values were found to be 80 Oe, 0.14 emu g −1 (at 8 kOe), and 9.0 × 10 −3 emu g −1, respectively. In order to realize the high-frequency applications of these materials, dielectric properties were measured in the frequency range of 1 Hz–1 MHz. The measured dielectric permittivity ( ε ′) and loss tangent (tan δ ) values of the composite polymer thin film were found to be 260 and 0.37 (at 1 kHz) respectively. The estimated dc conductivity ( σ d c) value was around 1.60 × 10 −8 S cm −1 .